2014
DOI: 10.1530/eje-14-0538
|View full text |Cite
|
Sign up to set email alerts
|

GH signaling in skeletal muscle and adipose tissue in healthy human subjects: impact of gender and age

Abstract: Objective: The mechanisms underlying the impact of age and gender on the GH-IGF1 axis remain unclear. We tested the hypothesis that age and gender have impacts on GH signaling in human subjects in vivo. Design: A total of 20 healthy non-obese adults ('young group' !30 years (5F/5M) and 'old group' O60 years (5F/5M)) were studied after: i) an i.v. GH bolus (0.5 mg) and ii) saline. Methods: Muscle and fat biopsies were obtained after 30 and 120 min. Total and phosphorylated STAT5B proteins, gene expression of IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Phosphorylation of STAT5 (pSTAT5) 30 min after GH was detected in seven of nine subjects (Figure a), but no pSTAT5 bands were detected 120 min after either GH or saline. Data on circulating GH and FFA levels from the entire study population have been reported previously (Vestergaard et al, ); in this study, we extracted data from the eight subjects, who contributed to microarray analysis. GH peaked in serum 5 min after its administration [95.1 ± 4.9 ug/l (mean ± SE)], and returned to baseline after 120 min (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of STAT5 (pSTAT5) 30 min after GH was detected in seven of nine subjects (Figure a), but no pSTAT5 bands were detected 120 min after either GH or saline. Data on circulating GH and FFA levels from the entire study population have been reported previously (Vestergaard et al, ); in this study, we extracted data from the eight subjects, who contributed to microarray analysis. GH peaked in serum 5 min after its administration [95.1 ± 4.9 ug/l (mean ± SE)], and returned to baseline after 120 min (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The human data derive from a clinical experiment from which data of a different nature have been published (Vestergaard et al, ). All subjects were studied in random order on two occasions after an overnight fast for 12 hr receiving an intravenous bolus of either GH (0.5 mg (Genotropin miniquick, Pfizer)) or saline.…”
Section: Methodsmentioning
confidence: 99%
“…This temporal pattern suggests that the effect involves regulation of gene expression in AT. We have consistently demonstrated that systemic GH acutely activates the STAT5 signaling pathway, which is considered the canonical pathway whereby GH regulates transcription of target genes [5], in human AT in vivo [6], [7], [8], [9], [10], [11]. In support of this, studies in rodents indicate that STAT5 is involved in GH-induced lipolysis [12], [13], [14], [15], but there are also in vitro studies to suggest that GH stimulates lipolysis via activation of the MAPK pathway [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both spontaneous and stimulated GH secretion in middle-aged adults is determined more by abdominal fat than by aging, so weight loss would help restore impaired GH secretion in obesity [8].…”
Section: Gh/igf-1 Axismentioning
confidence: 99%